Cell-free supernatant of Bacillus velezensis suppresses mycelial growth and reduces virulence of Botrytis cinerea by inducing oxidative stress - Zhao, Huanlan; Liu, Kui; Fan, Yezhen; Cao, Jiacan; Li, Huanghuan; Song, Wu; Liu, Yongsheng; Miao, Min (Frontiers in Microbiology, 2022)
As a notorious pathogenic fungus, Botrytis cinerea has been reported to infect more than 1400 species of plants and cause postharvest gray mold of numerous economic fruits, leading to substantial economic losses. Traditional chemical fungicides in pathogen control have potential issues regarding environmental pollution, disease resistance and human health. More safety and efficacious prevention technique of postharvest gray mold are in urgent demand. This study aims to investigate the potential function and mechanism of Bacillus velezensis to control gray mold for harvested fruits. The results showed that the cell-free supernatant (CFS) generated from B. velezensis strain A4 was able to inhibit spore germination, germ tube elongation and hyphal growth of B. cinerea in vitro, and impair the pathogenicity of B. cinerea on the four tested fruits. Further analysis demonstrated that CFS significantly reduced the expression of genes associated with growth and pathogenicity and weakened the ability of B. cinerea spores to penetrate plant cell walls in a dose-dependent manner. Moreover, the CFS destroyed the membrane of hyphae, resulting in exosmosis of cell contents and caused hyphal cells to accumulate excessive reactive oxygen species (ROS), leading to hyphal oxidative damage. Our findings indicate that B. velezensis CFS can damage B. cinerea mycelial cells by promoting excessive accumulation of ROS to realize its biological control function.